Industry 4.0: business and technological aspects of change (Journal of Universal Excellence, 2026)
Research Question (RQ): What are the key business and technological aspects of the changes brought about by the Industry 4.0 concept?Purpose: The aim of the research is to develop a model of an effective approach to managing the necessary changes and various aspects of digital transformation in industry.Method: In product development, companies use the approach of informatization and automation of business processes in managing changes, which is mainly focused on achieving technological changes. Such an approach is no longer appropriate and has become insufficient. We propose an approach that, in addition to the technological ones, also takes into account the business aspects of the necessary changes. Such an approach enables significantly better interaction between all stakeholders involved in change processes. As it arises from business motives, it also leads to significantly better results in industrial practice.Results: We developed a model of strategic and comprehensive approach to the necessary changes in the digital transformation of the company. We suggest considering aspects of strategy, business processes, technology, employees and organizational culture. The model takes into account various aspects of the necessary changes.Organization: Proposed model identifies the business and technological aspects of the necessary changes with the introduction of the Industry 4.0 concept in the company. It increases the likelihood of a successful digital transformation and directs change providers to address key content challenges.Society: The research increases the efficiency and effectiveness of the implementation of the company's digital transformation process. It ensures the identification and consideration of all essential elements of business renewal, which reduces project costs and improves the results of implemented changes. It emphasizes the role and importance of employees, which improves and develops the organizational culture of the company.Originality: Developed model builds on the existing approach to business renovation and computerization. It takes into account theoretical findings and experiences from projects that bring new insights and new challenges of digital transformation and development of the company into industrial practice.Limitations / further research: Proposed model has been tested and implemented in industrial practice. In the future, it would be sensible to upgrade its content in all five dimensions that it brings to the business and technological segment of dealing with the necessary changes.
Keywords: industry 4.0; digital transformation; business aspect of change; technological aspect of change